Analisis Produktifitas Pekerja Dengan Metode Produktifitas Parsial - Kevin Simanjuntak; Kusnadi Kusnadi (Jurnal Ilmiah Wahana Pendidikan, 2022)
PT XYZ is a business that specializes in the development of a wide range of different veterinary pharmaceuticals. It is possible to say that the quantity of output is unreliable, and evidence of this can be found in the production figures, which have both reduced and grown on a monthly basis. The purpose of this research is to conduct an investigation on PT XYZ's current levels of labor productivity. For the purpose of this research, the technique of partial productivity was used to determine the level of labor productivity for each month. Because the results of the computation are more than 100 percent or 1 (one) each month, the value of labor productivity in the production section on production outcomes throughout 2021 at PT. XYZ is satisfactory enough. The value of the whole workforce's partial productivity for one year is 69.54 percent, with an average value of 5.795 percent.